Parent-perceived neighbourhood environment, parenting practices and preschool-aged children physical activity and screen time: a cross-sectional study of two culturally and geographically diverse cities - Ester Cerin; Anthony Barnett; Tom Baranowski; Rebecca E. Lee; Robin R. Mellecker; Yi Nam Suen; Jason A. Mendoza; Deborah I. Thompson; Teresia M. O'Connor (BMC, 2022)
Abstract Background Preschool-aged children's physical activity (PA) and screen time (ST) are important health-related behaviours likely influenced by PA opportunities, parental perceptions of neighbourhood safety and parenting practices pertaining to PA and ST. How these factors interact to impact on young children's PA and ST, and whether their effects are generalisable across cultures and geographical location is not known. This study addressed these knowledge gaps by conducting pooled analyses of comparable data from two culturally and geographically diverse samples - Chinese parent-child dyads from an ultra-dense city (Hong Kong, China) and Latino parent-child dyads from a low-density city (Houston, USA). Methods The analytical sample consisted of 164 Hong Kong Chinese and 84 US Latino parent-child dyads with data on socio-demographic characteristics, parent-perceived neighbourhood destinations and facilities for children's PA, physical and social safety-related neighbourhood attributes, PA-related parenting practices and child's ST and accelerometer-assessed PA. Generalised linear models with robust standard errors accounting for neighbourhood-level clustering were used to estimate associations and interaction effects. Results Hong Kong Chinese children accumulated less PA than US Latino children, although the latter had more ST. Hong Kong Chinese parents reported more parenting practices promoting inactivity. Neighbourhood PA opportunities were positively related to children's PA only if parental perceptions of neighbourhood safety were favourable, and the associations of physical neighbourhood environment characteristics with children's PA and ST depended on PA-related parenting practices. Community cohesion was positively related to children's PA and negatively related to ST, while parental promotion of ST was positively associated with children's ST. Correlates of children's PA and ST did not differ by city. Conclusions The substantial differences in activity patterns between Hong Kong Chinese and US Latino preschool-aged children observed in this study are likely due to a combination of cultural and built environmental factors. However, the fact that no between-city differences in correlates of PA and ST were detected indicates that both populations of children are equally affected by parent-perceived neighbourhood environmental characteristics and parenting practices. Overall, this study highlights the importance of considering how various individual-, home- and neighbourhood physical and social factors interact to influence young children's health-promoting activity levels.